Aumento ósseo guiado com membrana de látex e reforço em titânio em associação com plasma rico em plaquetas e células-tronco mesenquimais de polpa de dente decíduo humano - Eleutério, Rachel Gomes (2010)
The natural latex extracted from Hevea brasiliensis is a biocompatible material. After polymerization, a film is formed with high mechanical strength, elasticity, flexibility, low cost, desirable characteristics for use as an occlusive membrane in guided bone regeneration (GBR) procedure. This work consists of the use of latex membrane molded into a dome shape, through titanium mesh, in combination with dental pulp mesenchymal stem cell l stem cells from human deciduous tooth and autogenous platelet rich plasma (PRP), to promote the guided bone augmentation, increasing the bone volume beyond the structure of the skeleton. For that purpose, eight New Zealand rabbits were used. Bilateral surgical bone defects were created in the outer cortical bone of the skull, with 8mm in diameter and containing nine holes inside it. Above the defects, the domes were adapted. One of them was filled with stem cells suspended in PRP and the other only with PRP. After 60 days, the animals were euthanized and the tissue inside the domes was evaluated microscopically by descriptive histology and histomorphometry. The bone formation above the native bone tissue was observed in both sides. Despite the quantitative measurement of newly formed bone does not indicate statistically significant differences (t-Student test), it was possible to observe more mature bone tissue on the side treated with stem cells, characterized by the presence of bone trabeculae widely covered by osteblasts and larger than the side treated only with PRP